Strategic Analysis in the Application of Digital Technology in Dental Practice - Nora Lelyana (PT FORMOSA CENDEKIA GLOBAL, 2023)
Digital technology's adoption in dental practices is unclear, but understanding its current level can offer insights into potential benefits, risks, and challenges. The study investigates the adoption and utilization of digital technology in dental practices, examining its impact on efficiency, potential risks, and benefits. It also aims to develop strategies for successful integration. This study uses a qualitative approach, analyzing knowledge, expert opinions, and real-world experiences on digital technology adoption in dental practices using secondary data from scholarly articles and industry reports. The current level of adoption and utilization of digital technology in dental practices varies widely. While some dental practices have fully embraced digital technology, others lag behind. The impact of digital technology on the efficiency and effectiveness of dental practice operations, such as appointment scheduling, record-keeping, and treatment planning, has been largely positive. However, numerous challenges exist, including data security and integration issues. Benefits and opportunities offered by digital technology include improved diagnostics, patient communication, and the overall patient experience. Digital technology has the potential to revolutionize dental practice operations and enhance patient care. Digital technology adoption in dental practices is varying, but challenges like data security and integration need to be addressed for successful integration and maximum benefits.